Robust sampled-data cruise control scheduling of high speed train - Li, Shukai; Yang, Lixing; Li, Keping; Gao, Ziyou (Transportation research. Part C, Emerging technologies, 2014)
•The high speed train is modeled by a cascade of cars connected by flexible couplers.•The robust sampled-data cruise control scheduling is designed with the form of LMIs.•The high speed train tracks the desired speed under the sampled-data cruise control.•The proposed method ensures the safety and comfort of the operating of high speed train. This paper investigates the robust cruise control scheduling of high speed train based on sampled-data. The dynamics model of a high speed train is modeled by a cascade of cars which are connected by flexible couplers, and is subject to rolling mechanical resistance, aerodynamic drag and wind gust. The robust cruise controller is designed for high speed train based on sampled-data. By using the method of converting the sampling period into a bounded time-varying delay, the addressed problem is transformed to the problem of stability analysis of time-varying delays system. Based on Lyapunov stability theory, sufficient conditions for the existence of robust sampled-data cruise control scheduling are given in terms of linear matrix inequality (LMI), under which the high speed train can track the desired speed, the relative spring displacement between the two neighbouring cars is robustly stable at the equilibrium state, and a prescribed H∞ disturbance attenuation level with respect to the wind gust is guaranteed, which ensures the safety and comfort of the operating of high speed train. Numerical examples are given to illustrate the effectiveness of the proposed methods.